Abdominal fat distribution and carotid atherosclerosis in a general population: a semi-automated method using magnetic resonance imaging. - Radmard, Amir; Poustchi, Hossein; Ansari, Leila; Khorasanizadeh, Faezeh; Yoonessi, Ali; Hashemi Taheri, Amir; Rahmanian, Mohammad; Jafari, Elham; Malekzadeh, Reza; Merat, Shahin; Radmard, Amir Reza; Hashemi Taheri, Amir Pejman; et al. (Japanese Journal of Radiology, 2016)
Purpose: Available evidence suggests functional differences in visceral and subcutaneous fat. We investigated the association between quantitative measures of central adiposity with indicators of carotid atherosclerosis including intima-media thickness (IMT) and plaque in a general population using a semi-automated method on magnetic resonance imaging (MRI) data.Methods: In this cross-sectional study 200 subjects (52 % female), aged 50-77 years, were randomly selected from Golestan Cohort Study. Participants underwent ultrasound examination of carotid arteries and abdominal MRI. Segmentation and calculation of visceral (VFA) and subcutaneous fat area (SFA) were performed on three levels using semi-automated software. Various conventional anthropometric indices were also measured.Results: Among 191 enrolled subjects, 77 (40 %) participants had IMT ≥0.8 mm. Carotid plaques were detected in 86 (44 %) subjects. In separate multivariate analysis models, unlike SFA and other anthropometric indices, the last tertile of VFA values was associated with at least threefold excess risk for IMT ≥0.8 mm (OR 3.8, 95 % CI 1.36-6.94, p = 0.02). There was no significant difference between mean values of categorized obesity indices in subjects with and without plaque, while participants in the highest tertile of VFA values were demonstrated to have higher risk of more than one plaque (OR 4.57, 95 % CI 1.03-20.11, p = 0.034).Conclusions: A higher amount of visceral fat, measured by a semi-automated technique using MRI, is associated with increased IMT and having more than one carotid plaque in a general population, while subcutaneous fat measures are poor indicators for identifying carotid atherosclerosis.